Rotavirus immunization: Global coverage and local barriers for implementation - Lo Vecchio, A; Liguoro, I; Dias, J; Berkley, J; Boey, C; Cohen, M; Cruchet, S; Salazar-Lindo, E; Podder, S; Sandhu, B; Sherman, P; Shimizu, T; et al. (Elsevier, 2017)
BACKGROUND: Rotavirus (RV) is a major agent of gastroenteritis and an important cause of child death worldwide. Immunization (RVI) has been available since 2006, and the Federation of International Societies of Gastroenterology Hepatology and Nutrition (FISPGHAN) identified RVI as a top priority for the control of diarrheal illness. A FISPGHAN working group on acute diarrhea aimed at estimating the current RVI coverage worldwide and identifying barriers to implementation at local level. METHODS: A survey was distributed to national experts in infectious diseases and health-care authorities (March 2015-April 2016), collecting information on local recommendations, costs and perception of barriers for implementation. RESULTS: Forty-nine of the 79 contacted countries (62% response rate) provided a complete analyzable data. RVI was recommended in 27/49 countries (55%). Although five countries have recommended RVI since 2006, a large number (16, 33%) included RVI in a National Immunization Schedule between 2012 and 2014. The costs of vaccination are covered by the government (39%), by the GAVI Alliance (10%) or public and private insurance (8%) in some countries. However, in most cases, immunization is paid by families (43%). Elevated cost of vaccine (49%) is the main barrier for implementation of RVI. High costs of vaccination (rs=-0.39, p=0.02) and coverage of expenses by families (rs=0.5, p=0.002) significantly correlate with a lower immunization rate. Limited perception of RV illness severity by the families (47%), public-health authorities (37%) or physicians (24%) and the timing of administration (16%) are further major barriers to large- scale RVI programs. CONCLUSIONS: After 10years since its introduction, the implementation of RVI is still unacceptably low and should remain a major target for global public health. Barriers to implementation vary according to setting. Nevertheless, public health authorities should promote education for caregivers and health-care providers and interact with local health authorities in order to implement RVI.